Pengaruh Tes Kemampuan Akademik (TKA) terhadap Minat Belajar Siswa Kejuruan Teknik Komputer dan Jaringan - Iman, Ahmad Sayyidul; Septiadi, Jaka (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
This study examines the influence of the Academic Ability Test (TKA) on the learning interest of Computer and Network Engineering (TKJ) students at SMKS TI Muhammadiyah Cikampek. Using a quantitative correlational design, data were collected from 109 students via official TKA score documentation and a 15-item Likert-scale learning interest questionnaire (Cronbach’s α = 0.8256). Simple linear regression analysis revealed no significant effect of the TKA on students’ learning interest (t = 1.505; p = 0.135 > 0.05), with R² = 0.021, indicating that TKA scores account for only 2.1% of interest variance. The findings suggest that vocational students’ learning interest is driven primarily by practical relevance and career motivation rather than standardized academic assessment performance. This study contributes empirical evidence on the disconnect between general academic standardization and the affective dimensions of vocational learners in the Indonesian context, underscoring the need for contextually aligned evaluation instruments in vocational education.